On sound change and gender: the case of vowel length variation in Scottish English - Florent Chevalier (Anglophonia)
The varieties of English spoken in Scotland have their own unique pattern of vowel duration, referred to as the Scottish Vowel Length Rule; this pattern differs from the one prevailing in most varieties of English. Considering the situation of permanent contact between Scotland and England, one could expect Scottish speakers to gradually adopt the Anglo-English pattern; several studies on the realisation of the SVLR have indicated this change is under way. However, the results of the single study using a corpus of Glaswegian English were at odds with this expectation. This study, focused solely on male speakers, demonstrated that the erosion of the SVLR in Glaswegian English did not result in a move towards Anglo-English patterns. It also highlighted the influence of prosodic factors on the evolution of vowel length. Our work seeks to extend that study to comparable female speakers, testing the same real-time and apparent-time perspectives. Results show that the SVLR is weakening more strongly for women than for men, and that the Anglo-English durational pattern is not gaining ground in Glaswegian. Furthermore, this study confirms the importance of prosodic factors in sound change.